2020
DOI: 10.1002/eem2.12127
|View full text |Cite
|
Sign up to set email alerts
|

Net‐C18: A Predicted Two‐Dimensional Planar Carbon Allotrope and Potential for an Anode in Lithium‐Ion Battery

Abstract: Net‐C18, a predicted two‐dimensional (2D) graphene‐like carbon allotrope, is investigated via first‐principles calculations. Its space group is Pmmm. There are 18 carbon atoms per cell. Net‐C18 has five‐, six‐, and eight‐membered rings. Net‐C18 may be formed by adding even pairs of carbon atoms on the top of hexagons to reconstruct new five‐ and eight‐membered rings, extending the strategy of Haeckelite. Compared to that of graphene (−9.28 eV atom−1), the total energy of net‐C18 (−9.15 eV atom−1) is only 0.13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The goal of being “carbon neutral” has prompted researchers to seek new energy conversion and storage systems that possess greener, more cost-effective production processes, for instance, for wind energy, solar energy, and electrochemical energy storage and so on. Among them, sodium-ion batteries (SIBs) based on Prussian blue analogue (PBA) cathodes with open three-dimensional crystal structures, high Na + storage capacity, and low cost have attracted much attention. …”
Section: Introductionmentioning
confidence: 99%
“…The goal of being “carbon neutral” has prompted researchers to seek new energy conversion and storage systems that possess greener, more cost-effective production processes, for instance, for wind energy, solar energy, and electrochemical energy storage and so on. Among them, sodium-ion batteries (SIBs) based on Prussian blue analogue (PBA) cathodes with open three-dimensional crystal structures, high Na + storage capacity, and low cost have attracted much attention. …”
Section: Introductionmentioning
confidence: 99%
“…Graphene, as a well-known two-dimensional (2D) nanomaterial having excellent physical and chemical properties, has been explored globally in recent years, including optoelectronics, sensing, energy, biomedicine, and other fields. 1−7 The discovery of graphene has stimulated the exploration of 2D materials, and many graphene-like structures were found, 8−10 such as net-C18, 11 wrinkled graphene, 12 hp-C18, 13 and pentagraphene. 14 In addition, the gapless graphene can become semiconducting upon doping with other atoms to extend the investigations of graphene-like structures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Graphene, as a well-known two-dimensional (2D) nanomaterial having excellent physical and chemical properties, has been explored globally in recent years, including optoelectronics, sensing, energy, biomedicine, and other fields. The discovery of graphene has stimulated the exploration of 2D materials, and many graphene-like structures were found, such as net-C18, wrinkled graphene, hp-C18, and penta-graphene . In addition, the gapless graphene can become semiconducting upon doping with other atoms to extend the investigations of graphene-like structures. Due to their atomic sizes close to carbon’s, nitrogen and boron atoms are widely used as dopants to form boron carbon nitrogen (BCN) compounds. , Many BCN materials with unique structures and excellent performance have been developed. A h-BCN material was synthesized by graphene and h-BN .…”
Section: Introductionmentioning
confidence: 99%
“…Perfect planar configurations have been viewed as a new class of potential candidates for the anode materials of LIBs and NIBs. The ab initio computations show that many planar 2D materials, such as NiC 3 monolayer and Net-C18, are potentially superior candidates for LIBs and NIBs. For example, Zhu et al identified a fully planar NiC 3 monolayer as a highly symmetric anode material, and the capacity for Li and Na reaches 1698 mAh g –1 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhu et al identified a fully planar NiC 3 monolayer as a highly symmetric anode material, and the capacity for Li and Na reaches 1698 mAh g –1 . Cai et al predicted a 2D graphene-like carbon allotrope of Net-C18 with a low energy barrier (0.32 eV), low open-circuit voltage (OCV; 0.024 V), and high theoretical specific capacity (403 mAh g –1 ) for LIBs. Although intensive investigations have been conducted, perfect planar structures with excellent performance are still under development in the area of NIBs.…”
Section: Introductionmentioning
confidence: 99%